2010
DOI: 10.21608/jappmu.2010.86191
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF SOURCE AND LEVEL OF DIETARY WATER HYACINTH ON NILE TILAPIA, Oreochromis niloticus, PERFORMANCE

Abstract: A feeding laboratorial trial in glass aquaria for 12 weeks, to replace graded levels of water hyacinth (WH) meal protein from two (polluted and not polluted) water sources instead of 0, 10, 20, 30 and 40% of soybean meal protein in Nile tilapia diets. Ten experimental diets were formulated to be isocaloric and isonitrogenous (26% crude protein) and offered daily at 2 meals, 6 days a week at 3% of fish biomass daily. Results indicated that rearing water did not influence fish by the tested treatments. Most test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Water hyacinth protein could also partially (10-20%) replace soybean meal protein realizing the best growth rates and economic efficiency (Abdelhamid et al, 2006). Yet, Abdelhamid et al (2010a & b) confirmed the opposite results; since the dietary inclusion of water hyacinth (particularly from polluted resources) negatively affected fish weight, their SGR, survival, feed conversion, and fish body composition. Consequently, they recommended to does not use water hyacinth from polluted water resources in fish nutrition, but when it is necessary and in case of feed shortage, it could be used only from uncontaminated resources and a maximum limit not exceed 30% of the dietary soybean meal protein.…”
Section: Final Live Body Weight Of the Experimental Fishmentioning
confidence: 68%
“…Water hyacinth protein could also partially (10-20%) replace soybean meal protein realizing the best growth rates and economic efficiency (Abdelhamid et al, 2006). Yet, Abdelhamid et al (2010a & b) confirmed the opposite results; since the dietary inclusion of water hyacinth (particularly from polluted resources) negatively affected fish weight, their SGR, survival, feed conversion, and fish body composition. Consequently, they recommended to does not use water hyacinth from polluted water resources in fish nutrition, but when it is necessary and in case of feed shortage, it could be used only from uncontaminated resources and a maximum limit not exceed 30% of the dietary soybean meal protein.…”
Section: Final Live Body Weight Of the Experimental Fishmentioning
confidence: 68%